Perancangan Knowledge Management Perawatan Dan Perbaikan Mesin Pompa Sentrifugal Menggunakan Metode Case Based Reasoning - Fathoni -; Syahrizal Dwi (Universitas Sriwijaya, 2018)
ABSTRACTThe utilization and existence of centrifugal machine pumps in the industrial world is very important to assist the production process, at least almost 75% of industries use this type of machine pump. As an operational tool in the industry, centrifugal pumps must be able to be used and maintained properly because the damage to the pumping machine causes the operational or production process to be not maximal even can lead to cessation of the production process, and the impact on financial losses are not small. This study aims to create a knowledge management design to assist in the manufacture of software so that ultimately can facilitate the users (technicians) centrifugal pump machine do maintenance and repair the machine. To achieve the purpose of the research the researcher uses the stages of research consisting of three stages, namely: Phase 1. Preparation and Identification of knowledge; Phase 2. Analysis and Design of Knowledge Management and Phase 3. Design of Knowledge Management Prototype. Meanwhile, to manage the knowledge and explicit knowledge of the researcher using Case-Based Reasoning (CBR) method by using Nearest Neighbor Retrieval algorithm to find the best solution in maintaining and repairing centrifugal pump machine by calculating the proximity between new technical constraints and the old technical obstacle already in the database. This study resulted in a knowledge management design consisting of functional requirements and flow and software algorithms to assist application developers in the creation of knowledge management software interfaces to maintain and repair centrifugal pump machines.Keywords: Centrifugal Pump Machine, Knowledge Management, Case-Based Reasoning